Pelaksanaan Tugas dan Fungsi Dinas Perhubungan Kota Kupang Terhadap Pengendara Bermotor Sambil Merokok dan Menelepon - Rudolf Mourits Christian Piero Lanoe; Saryono Yohanes; Yosef Mario Monteiro (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
Driving discipline is an important attitude that must be possessed by all drivers or drivers in order to arrive safely at their destination. Traffic violations still occur frequently, one of which is smoking and calling while driving. The Transportation Service is an implementing element of the Regional Government in the field of Transportation which has the main task, namely Organizing Government affairs in the field of land, sea and air transportation, in accordance with the Laws and Regulations. This type of research shows empirical juridical research, with data collection techniques through interviews, observations, and literature/document studies. The data collected is analyzed descriptively, the data that has been processed will be analyzed using the descriptive analysis method. The results of this study show: (1) The implementation of the duties and functions of the Kupang City Transportation Office for motorcyclists who smoke and call while driving is not / or has not been effective in accordance with the provisions of applicable laws and regulations. (2) There are several factors that hinder the implementation of the duties and functions of the Kupang City Transportation Office for motorcyclists who smoke and call while driving, including the legal factors themselves and the factors of facilities and infrastructure, namely the main obstacle is the unavailability of the budget. These two factors certainly have an interest that always hinders or affects the implementation of the rules regarding the prohibition of smoking and calling while driving, making the rules ineffective. Based on the results of the research, the author has several suggestions, namely improving the implementation of duties and functions for motorcyclists who smoke and call while driving, in accordance with the provisions of applicable laws and regulations and add educational programs and campaigns in the community related to the dangers of smoking and calling while driving, in addition to law enforcement must be carried out consistently by providing clear sanctions so that it has a deterrent effect, and local governments need to allocate budgets to improve facilities and infrastructure that support control.